2022
DOI: 10.1039/d1tc05863k
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy: fermi level control to realize 3D pyramidal NiCo-LDH/ReS2/n-PSi as a high-performance photoanode for the oxygen evolution reaction

Abstract: Loading ReS2 nanosheets (NSs) on planar p-type doping Si substrate has been proved that it can work well in photoelectrochemical (PEC) water splitting for hydrogen evolution reaction (HER). High PEC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The common precursors for the CVD synthesis of ReS 2 are ammonium rhenate (NH 4 ReO 4 ), Re powder [ 82 ], and rhenium-containing oxides (ReO 3 or Re 2 O 7 ), with sulfur powder used as the predominant sulfur source and heated in a different zone [ 33 , 85 , 86 ]. The ReS 2 prepared via the CVD method exists mostly in petal-like ReS 2 nanowalls arranged vertically without agglomeration [ 28 , 33 , 87 ]. Zhang et al anchored the ReS 2 nanowalls vertically on the surface of the Si/SiO 2 substrate ( Figure 2 i), which can distribute ultra-uniformly with a dense structure over a wide area ( Figure 2 j) [ 33 ].…”
Section: Synthetic Methods For Res 2 and Its Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The common precursors for the CVD synthesis of ReS 2 are ammonium rhenate (NH 4 ReO 4 ), Re powder [ 82 ], and rhenium-containing oxides (ReO 3 or Re 2 O 7 ), with sulfur powder used as the predominant sulfur source and heated in a different zone [ 33 , 85 , 86 ]. The ReS 2 prepared via the CVD method exists mostly in petal-like ReS 2 nanowalls arranged vertically without agglomeration [ 28 , 33 , 87 ]. Zhang et al anchored the ReS 2 nanowalls vertically on the surface of the Si/SiO 2 substrate ( Figure 2 i), which can distribute ultra-uniformly with a dense structure over a wide area ( Figure 2 j) [ 33 ].…”
Section: Synthetic Methods For Res 2 and Its Compo...mentioning
confidence: 99%
“…The beneficial exposure of the (001) facet ensured that more active sites were accessible for hydrogen adsorption, consequently enhancing the catalytic activity. The growth of the ReS 2 single-crystal nanosheets does not need a polished substrate or a small lattice mismatch [ 87 ]. Cheng et al grew ReS 2 tightly on the TiO 2 -coated b-Si substrate with the shape of nanopyramids via the CVD method.…”
Section: Synthetic Methods For Res 2 and Its Compo...mentioning
confidence: 99%
“…The pyramidal pattern of Si provides a 3D antireflection structure. Finally, a NiCo layered double hydroxide (LDH) was electrodeposited on the ReS 2 /n-PSi to enhance the photocurrent as a cocatalyst and protective layer . The catalytic activity of the electrode was measured in a 0.5 M Na 2 SO 4 aqueous solution.…”
Section: Rhenium For Oermentioning
confidence: 99%
“…, in conjunction with the release of gaseous oxygen (eqn (7)). Subsequently, the absorption profiles labeled as d suggested that the overall oxidation state of iridium ion was increased again.…”
Section: àmentioning
confidence: 99%
“…The fabrication of iridium oxide has been explored for several decades in applications including water splitting and pseudocapacitors. [1][2][3][4][5][6][7][8][9] It is because the iridium oxide is known as a conductive oxide with superb chemical inertness and electrocatalytic activity. Recently, owing to its impressive biocompatibility, the iridium oxide has been considered as a bio-stimulating electrode in implantable bio-electronics whose function is to provide electrical charges to stimulate neurons for the mitigation or remedy of neuronal disorders.…”
Section: Introductionmentioning
confidence: 99%